Does Bitcoin Follow the Market Conditions Anymore? - ERCAN, Harun (Journal of Advanced Studies in Finance, 2019)
Recent research on the economics of digitization investigates the dramatic changes in markets by digital technology. Digital technology has caused significant differences in in the cost of storage, computation, and transmission of data. As one of the latest sign of digitization in our life, the use of cryptocurrencies has been drawing attention of all market players. Blockchain technology is recently reallocating resources, restructuring of routines, changing market relationships and patterns of the flow of goods and services. This study investigates the coherence of Bitcoin with the movements of the main indicators of different markets. Aim of this research is to clarify whether this cryptocurrency follows the market conditions or not. Because the movements of the market values of Bitcoin are aimed to be investigated to show that they can be used separately as a tool of risk management. For this reason, wavelet analysis has been employed to define cross-correlation between time series of the daily USD value of Bitcoin and some market indicators. Some literature asserts that Bitcoin has recently started to follow market conditions. If Bitcoin process follows the market conditions more than before, that if This analysis will explain if there is a change in hedging possibility of Bitcoin recently.